Distribution and Diversity of Macroalgae in Seagrass and Coral Reef Ecosystems on the Coast - Mayakun, Karel; Prathep, Sutthawan (BIOEDUSCIENCE, 2023)
Background: This article was withdrawn because there were indications of falsification of data and plagiarism at the request of the author.